Social Networks for Library Promotion - Irawati, Ina (2012)
This paper intends to discuss about social networks for promotion of library. Library as an information center has responsibility to collect, to process, and to disseminate of information to the community. Library can use the development of information technology to promote their collection, their activities, and their services to the user. Promotion is an activity to disseminate information about the products so consumer can get and use them. Besides promotion by mass media, brochures, and exhibitions, social networks are believed can be used to disseminate information about library more widely and attract more public attention. The existence of social networks is an opportunities for library to increase services to the user. This paper will be focus on facebook as a tool of library promotion because facebook is a popular social networks in Indonesia. In Indonesia, facebook user about 43 million people. So, they are potensial user for library. Facebook has been used by business firms to promote their product, to discuss with consumer, and to get feed back about their product from consumer. So did the library, for example, The Japan Foundation Library in Jakarta, National Library of Indonesia. The results of brief observation can be seen that facebook in library is useful to promote library’s collection, activities and services. Facebook is preferred by user because it is more interactive.